PELAKSANAAN KEGIATAN TADRIB DAKWAH TERHADAP KEMAMPUAN DAKWAH MAHASISWA LDM AL-MADANI IAIN PAREPARE ANGKATAN 2020 - Sonia, Sonia; Fahru Raji; Amran Thamrin; Muhammad Sahid (Communication and Islamic Broadcasting Studies IAIN Parepare, 2024)
Tadrib da'wah activities held by the Al-Madani Student Da'wah Institute (LDM), this activity is an annual work program that must be followed by each of its cadres and is a requirement for members who later wish to become administrators in the organization, both new cadres and old cadres who Never participated in this activity before. Da'wah is a call to the way of Allah, an activity to invite and call people to Islam, so that people get a good way of life and are blessed by Allah SWT. So that his life and life while in the world and the hereafter, because the essence of the afterlife is eternal life.